[PP.24.10] LEFT VENTRICULAR DIASTOLIC FUNCTION IN RELATION TO HEMODYNAMIC LOAD COMPONENTS IN A GENERAL POPULATION. (September 2017) - Cauwenberghs, N.; Knez, J.; D'Hooge, J.; Thijs, L.; Staessen, J.A.; Kuznetsova, T.
Abstract : Objective: It was suggested that the contribution of central pulsatility to left ventricular (LV) diastolic dysfunction might be mediated by the hemodynamic loads of forward and backward (reflected) pulse waves and their ratio. Therefore, in the general population study, we investigated the relation between echocardiographic indexes of LV diastolic function and central hemodynamic components derived by flow-independent wave separation analysis. Design and method: In 755 participants, using echocardiography, we assessed LV dimensions, transmitral blood flow and mitral annular tissue Doppler velocities. From the central pressure waveform obtained by radial applanation tonometry, we derived central pulse pressure (cPP). Forward (Pf) and backward (Pb) wave amplitudes and their ratio (i.e. reflection magnitude, RM) were derived using triangular-flow wave separation analysis as implemented in SphygmoCor® software. Despite good quality of pulse wave recordings, the wave separation algorithm failed to retrieve Pf and Pb in 139 subjects (18.4%). Thus, this analysis included 616 subjects (46.1% women; mean age, 49.2 years). Results: Age explained most of the variance in cPP (24.6%), Pb (33.2%) and RM (36.1%; P < 0.0001 for all), but was not correlated with Pf. We also observed that age altered direct correlation between Pf and Pb (Pint < 0.0001). Other independent clinical correlates of cPP, Pf, Pb and RM were body mass index, heart rate, mean arterial pressure and use of antihypertensive drugs. In multivariable-adjusted analyses, transmitral early (E) and late (A) diastolic peak velocity and E/e' ratio (reflecting LV filling pressure) increased with amplitudes of cPP, Pf and Pb in both men and women (P < 0.025). Of all LV diastolic indexes, only E/A ratio was independently associated with RM in men (P = 0.019). After full adjustment, LV mass index increased with cPP and Pb in men only (P < 0.040). Conclusions: Low feasibility of yielding Pf and Pb amplitudes from pulse curves by the current triangular-flow algorithm might limit the clinical utility of this approach. We demonstrated that LV diastolic function indexes were related to both forward and backward wave amplitudes, favoring the use of the composite central pulse wave for prediction of LV diastolic dysfunction.